Highly efficient degradation of trichloroethylene in groundwater based on persulfate activation by polyvinylpyrrolidone functionalized Fe/Cu bimetallic nanoparticles. Issue 4 (August 2021) - Idrees, Ayesha; Shan, Ali; Ali, Meesam; Abbas, Zain; Shahzad, Tanvir; Hussain, Sabir; Mahmood, Faisal; Farooq, Usman; Danish, Muhammad; Lyu, Shuguang
Abstract: Polyvinylpyrrolidone coated nano zero valent iron-copper (PVP-nZVI-Cu) bimetallic nanoparticles were successfully synthesized for dechlorination of trichloroethylene (TCE) into non-toxic byproducts in the presence of persulfate oxidant. The average size of PVP-nZVI-Cu nanoparticles (3–25 nm) was smaller than PVP-nZVI (25–60 nm) and nZVI (50–90 nm) particles due to PVP role in the prevention of iron aggregation and agglomerations. The synthesized PVP-nZVI-Cu nanoparticles were used as an efficient persulfate (PS) activator to generate reactive oxygen species (ROSs) for the degradation of TCE. The complete removal of TCE (99.6%) was achieved in the presence of 0.4 g/L of PVP-nZVI-Cu nanoparticles and 6 mM of persulfate oxidant at acidic pH (3.2) with 82.3% of TCE dechlorination and 84.4% of total organic carbon (TOC) removal within 1 h. Further, the catalytic activity of PVP-nZVI-Cu particles for TCE removal in the presence of four surfactants (TW-80, BRIJ-35, TX-100, and SDS) was also investigated, showing 99%, 83%, 65% and 70% removal of TCE, respectively. The intermediate products of TCE elucidated by GC-MS investigation, i.e., dichloroacetic acid, vinyle chloride, oxalic acid and glyoxylic acid, further transformed into chloride ions, carbon dioxide and water as environmentally friendly end products. The scavenging results revealed that both OH and SO4 — radicals primarily contributed to TCE removal that was further confirmed with EPR analysis. Finally, the test of TCE removal in real groundwater validated that PS/PVP-nZVI-Cu system has significant potential and can be applied for remediation of TCE contaminated groundwater in in-situ practice. Graphical Abstract: ga1 Highlights: PVP functionalized Fe/Cu bimetallic nanoparticles were prepared. Particle size of PVP-nZVI-Cu (3–25 nm) was smaller than nZVI (50–90 nm). PVP-nZVI-Cu completely removed TCE in the presence of surfactant (TW-80). OH and SO4 — radicals contributed to the degradation of TCE.